Europe on the crossroads : Policy of deepening integration on the background of socio-economic context and politics in member states - Żukrowska, Katarzyna (Europa na rozdrożu : polityka pogłębiania integracji na tle społeczno-gospodarczym i politycznym państw Unii Europejskiej, 2018)
EU has presented five scenarios from which only one can be used as a guideline for the future path of European integration. None of the five scenarios has been selected as the one that will be followed in the future since the time they were shown to the public in March 2017. EU documents indicate that preferences are clear and “Europe plans to do more and together with all”. A similar situation is indicated by the context of closer cooperation between NATO and the EU. Nevertheless such a choice does not seem to get the uphold as far as the political situation in most of the EU states shows. The aim of this article is to present the conditions that will be used as a starting point for the formulation of three possible scenarios: most probable, pessimistic and optimistic
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 523, s. 430-443
Keywords: scenarios for the future EU integration; costs of future models of EU integration; internal market; EU-NATO cooperation; political integration of EU; scenariusze przyszłej integracji UE; koszty modeli przyszłej integracji UE; rynek wewnętrzny; współpraca UE-NATO; polityczna integracja UE